Teachers’ Perspective on Distance Learning for Students with Visual Impairment - Nur-Amija A. Adin; Eila Marie S. Enriquez; Julius Victor P. Ribo; Crizy Jane Quililan; Shenn ryne Gemarangan; Lyka Saldariega; Juspher Handang; Cherry Ann Doren (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Learners with special needs have come a long way in their education. It can be in the style of a strategy from special education (SPED) to curriculum implementation, or it can be in the form of a transition from integrated education to inclusive classrooms. The transition from traditional learning to a new mode of learning happened due to the rise of the Covid pandemic in 2019 until the present. Students were forced not to enter school to avoid the spread of the virus. With that as an alternative solution for learning, the Department of Education (DepEd) implemented distance learning and modular learning for all the students all over the Philippines including the learners with disabilities. The current research study aimed to identify the extent of distance learning for children with a visual impairment from their teacher’s point of view. The researchers used a qualitative case study method and distributed questionnaires to the three chosen respondents. A purposive sampling method was adopted to select the respondents. The researchers selected the Special educators who have experience in handling students with visual impairment during distance learning. Each of the teachers underwent formal interviews through Google Meet and some were written answers which were later transcribed and analyzed by the researchers. After conducting the data analysis, it became evident that many of the teachers have their own unique perspectives when it comes to their experiences, challenges, and coping strategies for distance learning for their students. Recommendations are made to provide solutions aimed at reducing conflict in implementing distance learning among students with visual impairment.